2014
DOI: 10.1016/j.foodcont.2013.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on the effectiveness of whey protein/glycerol edible films containing potassium sorbate to control non-O157 shiga toxin-producing Escherichia coli in ready-to-eat foods

Abstract: Potassium sorbate (PS) (0.5%, 1.0% and 1.5% w/w) was included into whey protein concentrate (WPC)/glycerol (Gly) edible films at pH 5.2 and 6.0. The films inhibited or retarded the growth of Shiga toxin producing Escherichia coli (STEC) pathogens in both diffusion and barrier tests. Bacterial growth inhibition was dependent on PS content at both pH values. PS release was not affected by pH. Scanning electron microscopy (SEM) was used to analyze the microstructure of the films and gain a better understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 39 publications
5
30
1
Order By: Relevance
“…It is important to note that SPI films were the only one of the control films that exhibited wax bloom visible to the naked eye, which, however, was reduced after addition of KS. In accordance with the present results, previous studies on whey protein films have also demonstrated that the addition of KS (0.5-1.5 %) could enhance film transparency (Pérez et al 2014). It was an interesting observation that the addition of KS significantly enhanced UV-blocking properties (especially in the middle UV) of all tested films.…”
Section: Light Transmission and Film Opacitysupporting
confidence: 92%
See 3 more Smart Citations
“…It is important to note that SPI films were the only one of the control films that exhibited wax bloom visible to the naked eye, which, however, was reduced after addition of KS. In accordance with the present results, previous studies on whey protein films have also demonstrated that the addition of KS (0.5-1.5 %) could enhance film transparency (Pérez et al 2014). It was an interesting observation that the addition of KS significantly enhanced UV-blocking properties (especially in the middle UV) of all tested films.…”
Section: Light Transmission and Film Opacitysupporting
confidence: 92%
“…The results of our study seem to be partially consistent with these findings. In a study described by Pérez et al (2014), the MICs of KS for pathogenic strains of E. coli at pH 6.0 were 2.5-5.0 mg/ml. These authors showed that the activity of KS was strongly dependent on pH; the KS concentrations needed to inhibit microbial growth in a liquid medium at pH 6.0 was 2-4 levels higher than at pH 5.2.…”
Section: Mic and Mbc/mfcmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, they have a great capacity to form films (Chen et al, 1995;Pérez et al, 2002;Javanmard, 2009). Because of the fact that they are edible and biodegradable, using whey proteins to manufacture films has gained a great deal of popularity among producers (Krochta and Mulder-Johnston, 1997;Ramos et al, 2012;Pérez et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%